The cult of the leader : a manifesto for more authentic business - Bones, Chris, 1958- (Hoboken, N.J. : Wiley, 2011)
In The Cult of the Leader Chris Bones argues that in order to rebuild trust and confidence, we need to redefine talent, revalue experience and reconsider remuneration. Only by doing this, will we come to a realistic appreciation of what leaders can and can't do. --Book Jacket.
Introduction : the gods that failed -- Practically perfect in every way : the making of the modern leader -- Because we're worth it : the rise of the L'Oreal generation -- Why didn't we see it coming? : the loss of liability, stewardship and owner control -- The public gets what the public wants : values, confidence, trust and reputation in leadership -- The manifesto for a more authentic business -- Diamonds on the soles of your shoes : the real war for talent -- Moving from warm gestures to cold showers : a reframing of executive reward -- Less is more : the future of leadership and its development in organizations -- Conclusion : the importance of being earnest : the price of the cult and the value of leadership.
Includes bibliographical (p. [241]-255) references.
Keywords: Leadership; Executive ability